Aneurysm Shrinkage Is Compatible With Massive Endoleak in the Presence of an Aortocaval Fistula: Potential Therapeutic Implications for Endoleaks and Spinal Cord Ischemia. (June 2016) - Sveinsson, Magnus; Sonesson, Björn; Resch, Timothy A.; Dias, Nuno V.; Holst, Jan; Malina, Martin
Purpose: To present a patient with ruptured abdominal aortic aneurysm (AAA) and aortocaval fistula who was successfully treated with endovascular aneurysm repair in spite of developing a massive endoleak.Case Report: A 70-year-old man with ruptured AAA and aortocaval fistula was treated with endovascular aneurysm repair (EVAR). During 8 years of follow-up, he had massive perfusion of the aneurysm sac by retrograde flow from the inferior mesenteric artery into the caval vein through the aortocaval fistula. The aneurysm diameter decreased continuously in spite of the type II endoleak. This observation illustrates the mechanisms of sac expansion and may have therapeutic implications for complicated type II endoleaks and prevention of spinal cord ischemia in thoracic stent-grafting.Conclusion: EVAR can be applied in this rare setting because the ensuing high-flow endoleak is associated with sac shrinkage owing to depressurization by the caval shunt.